APPLICATION OF THE ADDIE MODEL IN DESIGNING DIGITAL TEACHING MATERIALS - Diana Rossa Martatiyana, Herlina Usman, Hasanah Dewi Lestari (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2023)
Teaching materials are one of the important components in the learning process. The right teaching materials must support the smooth running of learning activities. The use of teaching materials needs to be adjusted to the conditions and characteristics of students. In designing or developing teaching materials, it requires an appropriate development model to ensure the quality of teaching materials and support the learning process. The ADDIE model can develop teaching materials according to the needs of students with the first stage of analysis, design, develop, implement, and end with Evaluate whose stages are equipped with revision activities first. This model can be used to develop digital teaching materials. This article aims to find out the role of the ADDIE model in designing digital teaching materials. The benefits of this research are to provide an understanding of the application of the ADDIE model in designing teaching materials, especially digital teaching materials. It is hoped that this research can be useful for all relevant parties, especially education stakeholders. This research uses the method of literature study or literature review by analyzing, collecting data from scientific articles related to research topics and problems. The results showed that the application of the ADDIE model can help in designing and compiling good and effective digital teaching materials for use in the learning process and addie steps are more systematic to be applied.